Platelet-rich plasma and bone morphogenetic protein: bucomaxillofacial and bone regeneration - Yaguana Galarraga, Daniel Alfonso (2022)
Introduction: Science has evolved at an accelerated pace in the last decades, due to the need to know more and more the human being and the environment that surrounds them. In the search for this knowledge, aiming to improve the quality of life and the treatment of diseases previously considered incurable, research, especially in the field of biotechnology, has transformed the day-to-day health professionals. The application of this biotechnology related to growth factors can be exemplified in the use of platelet-rich plasma (PRP), gel capable of modulating and accelerating some repair processes. Objective: The objective of this work was to review the concepts related to growth factors, as well as in relation to platelet-rich plasma as an adjuvant in bone regeneration therapies. Methods: The present study followed a systematic review model, following the rules of systematic review – PRISMA. This study focuses on the treatment of bone regeneration through platelet-rich plasma and morphogenetic protein (BMP). To this end, a survey was conducted in scientific articles in the databases PubMed, Medline, Scielo, Lilacs, and e-books. The Cochrane Instrument was used to assess the risk of bias of the included studies, and GRADE was used to classify the quality of articles to the type of study and scientific evidence. Results and Conclusion: Therefore, the use of PRP, which would accelerate the rate of bone formation, with bone morphogenetic proteins (BMPs), recombinant or autogenous, should be quite important and elucidative. The development of new research, seeking to use all known technology, will always be the best way for a short future to recognize what should be incorporated into the daily routine of medical and dental clinics, differing from what, for various reasons, whether it was just a marketing procedure or something. The greatest advantage of the use of platelet-rich plasma is its ability to accelerate the process of bone regeneration by increasing the number of growth factors present in human platelets. On the other hand, it is observed that one of its major disadvantages is the low life expectancy of these platelets in the recipient or graft bed. However, it is also known that the PRP technique would only accelerate a process of bone regeneration that normally already occurs and this process follows its path until the formation of the mature bone.